Approximate Normality of Low Degree Polynomials in Normal Independent Variables - Ferreira, Dário (2020)
In this paper, we emphasize that polynomials are asymptotically linear functions and show, through Monte Carlo methods, that when the variation coefficients are small, low degree polynomials in normal independent variables are approximately normal. An application which illustrates the approach is presented.